PENGARUH LITERASI KEUANGANN, KOMPETENSI SUMBER DAYA MANUSIA, DAN PENGGUNAAN FINANCIAL TECHNOLOGY TERHADAP KINERJA KEUANGAN UMKM DI BUKITTINGGI - Nadia Oktaviani; Rika Widianita (Adisam Publisher, 2024)
Low financial performance is just one of many issues that micro, small, and medium- sized enterprises (MSMEs) in Bukittinggi confront. This is due to inefficient use of financial technology, a lack of financial awareness, and competent human resources. Micro, small, and medium enterprises (MSMEs) in Bukittinggi are the focus of this study, which aims to shed light on the relationship between financial literacy, HR competency, and the use of financial technology on their financial performance. The findings could have implications for both the regional and national economies. The government, financial institutions that assist MSME owners, and anybody else interested in this topic might find these answers useful. From a total of 7,473 individuals, 100 were chosen at random for this quantitative investigation. Data is gathered through the use of questionnaires. This research finds that financial literacy significantly impacts the financial performance of MSMEs in Bukittinggi, as indicated by a T value of 3.459 > 1.1986 and a sig value of 0.001 < 0.05. The financial performance of MSMEs in Bukittinggi is positively and significantly impacted by human resource competency, as evidenced by a T value of 2.030 > 1.1986 and a sig value of 0.045 <0.05. A T value of 3.451 > 1.1986 and a sig value of 0.001 < 0.05 imply that the implementation of financial technology has a positive and substantial impact on the financial performance of MSMEs in Bukittinggi. The f-table value is 2.70 and the sig value is 0.000, which is less than 0.05. This suggests that MSMEs in Bukittinggi are significantly impacted by financial literacy, human resource competency, and the utilization of financial technology. The data shows that 58.3% of the variance in MSME financial performance measures is explained by differences in financial literacy, human resource competency, and the usage of financial technology. The remaining 41.7% is influenced by or explained by other, less studied variables.